Impact of Placenta Previa on Neonatal and Maternal Health - Sumeeta; Ali, Sania; Gul, Shumail; Mal, Huna Gangu; Sakeena; Fatima, Aryan; Raishem (Indus Journal of Bioscience Research, 2025)
Background: Placenta previa, increasingly linked to prior caesarean section, is a major driver of peripartum haemorrhage, transfusion and hysterectomy, with downstream neonatal risks from prematurity and intensive care. Objective: To quantify maternal and neonatal outcomes associated with placenta previa and suspected placenta accreta spectrum (PAS), and to identify practice factors associated with morbidity in a tertiary centre, PUMHS Nawab Shah. Methods: Analytical cohort was conducted at the Department of Obstetrics & Gynaecology, PUMHS (Shaheed Benazirabad) over six months (9 Jul 2024–9 Jan 2025). We analysed 150 consecutive ultrasound-diagnosed low-lying/previa pregnancies. Data were abstracted using a standard proforma. Descriptive summarised case mix; χ²/Fisher’s exact and Mann–Whitney/Kruskal–Wallis compared groups; selected logistic models explored adjusted associations (α=0.05). Results: Complete/major previa comprised 42.0%; anterior implantation 54.0%; PAS suspected 42.7%. Median quantified blood loss was 1691 ml (IQR 1210–2050); PPH≥1000 ml 88.7%, transfusion 90.0%, hysterectomy 14.7%, ICU 18.7%. Gestational age was 35.9±1.9 weeks; preterm <37w 72.7%; NICU admission 70.7%; Apgar<7 at 5 min 11.3%. PAS suspicion was associated with higher NICU use (χ² p=0.0000) and greater maternal morbidity; QBL differed across placenta types (Kruskal–Wallis p=0.0000). Conclusions and implications: In this high-risk cohort, placenta previa especially with anterior location and PAS suspicion was associated with heavy bleeding, transfusion, and intensive care, alongside substantial prematurity and NICU demand. Findings support strengthening antenatal mapping and PAS pathways, planned team-based delivery, neuraxial anaesthesia where feasible, and haemorrhage bundles (including timely TXA) within Pakistan’s tertiary network.